2023
DOI: 10.3311/ppci.21756
|View full text |Cite
|
Sign up to set email alerts
|

Robust Vibration Output-only Structural Health Monitoring Framework Based on Multi-modal Feature Fusion and Self-learning

Abstract: Output-only structural health monitoring is a highly active research direction because it is a promising methodology for building digital twin applications providing near-real-time monitoring results of the structure. However, one of the technical bottlenecks is how to work effectively with multiple high-dimensional vibration signals. To address this question, this study develops a two-stage data-driven framework based on various advanced techniques, such as time-series feature extractions, self-learning, grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It is possible to include more features in the data to improve the detection accuracy; on the other hand, a feature importance study could be carried out to assess the contribution of every feature, and irrelevant ones could be discarded accordingly. A more in-depth study about feature extraction could be found in [24].…”
Section: Extracting Damage-sensitive Features From Vibration Signalsmentioning
confidence: 99%
“…It is possible to include more features in the data to improve the detection accuracy; on the other hand, a feature importance study could be carried out to assess the contribution of every feature, and irrelevant ones could be discarded accordingly. A more in-depth study about feature extraction could be found in [24].…”
Section: Extracting Damage-sensitive Features From Vibration Signalsmentioning
confidence: 99%